Opposing narratives about children's digital media use: a critical discourse analysis of online public advice given to parents in Australia and Belgium. (August 2020) - Zaman, Bieke; Holloway, Donell; Green, Lelia; Jaunzems, Kelly; Vanwynsberghe, Hadewijch
What are the public discourses about parental guidance of children's digital media use in Australia and Belgium? The findings of a multi-method interpretive content analysis suggest that both risks and opportunities are made significant, (re-)claiming power for parents to decide what is realistic. Belgian critical-optimistic commentary suggests that it is normal to see a variety of parenting practices in society, encouraging parents to make informed decisions considering the child's developmental age and mutual trust. Australian public commentary features emotionally laden, opposing views, whereby restriction seems the golden rule for guiding young children's engagement with digital media. Across the 30 months of the dataset, however, Australian pieces began to give voice to experts who embrace more relaxed rules. The study illuminates how public narratives are sites of political manoeuvring, revealing ideological stances relating to parental mediation and children's media use, sensitive to and reflective of situated meanings bound by space and time.